2015
DOI: 10.1093/eurheartj/ehv451
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia and atrial fibrillation in patients with stable coronary artery disease treated with ivabradine: an analysis from the SIGNIFY study

Abstract: ISRCTN61576291.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
3
21
0
3
Order By: Relevance
“…However, Martin et al have conducted a Meta analysis of five randomized trials with ivabradine, and reported a 15% increase in the relative risk of developing AF in patients receiving ivabradine. Another study performed by Fox et al showed that the incidence of emergent AF on ivabradine treatment group was similar with that of the placebo group (2.2% per year ivabradine vs 1.5% per year placebo) in patients with stable coronary artery disease. Ivabradine was also found to decrease the sinoatrial functions while inhibiting the I f current, and thus increase the risk of AF, which was in contrast to our results.…”
Section: Discussionmentioning
confidence: 77%
“…However, Martin et al have conducted a Meta analysis of five randomized trials with ivabradine, and reported a 15% increase in the relative risk of developing AF in patients receiving ivabradine. Another study performed by Fox et al showed that the incidence of emergent AF on ivabradine treatment group was similar with that of the placebo group (2.2% per year ivabradine vs 1.5% per year placebo) in patients with stable coronary artery disease. Ivabradine was also found to decrease the sinoatrial functions while inhibiting the I f current, and thus increase the risk of AF, which was in contrast to our results.…”
Section: Discussionmentioning
confidence: 77%
“…Показано, что на фоне оптимальной терапии снижение ЧСС ниже 70 уд/мин за счет дополнительного назначения ивабрадина ассоциировалось со снижением риска развития фатальных и нефатальных коронарных катастроф на 36% и необходимости в реваскуляризации на 30% (p=0,001). Тем не менее, по данным исследования SIGNIFY [15], проведенного на 18 тыс. пациентов в 2014 г. при отсутствии проявлений недостаточности кровообращения аргументации в пользу улучшения прогноза не получено.…”
Section: Discussionunclassified
“…60 When only emergent atrial fibrillation in SIGNIFY was considered, 74% of patients had no history of atrial fibrillation, and most cases were paroxysmal. 58 Although the incidence of the primary composite end point and stroke was comparable for those who developed atrial fibrillation on ivabradine and on placebo in SIGNIFY, this analysis lacked power, and a detectable downstream harm may manifest only when a large population can be analyzed for a longer duration.…”
Section: Adverse Eventsmentioning
confidence: 97%
“…Fortunately, no association was found between emergent bradycardia (HR <50 bpm) and the primary SIGNIFY end point, either in the total population or in those with activity-limiting angina. 58 Given the worse prognosis for patients with HF and atrial fibrillation compared with those with HF alone, the 1.5% absolute risk increase in atrial fibrillation over 28 months with ivabradine therapy (0.7% yearly absolute increased risk) in SIGNIFY is striking. 45,59 In the pooled analysis from SHIFT and BEAUTIFUL with baseline HR ≥70 bpm, there was a similar 1.7% increase in the absolute risk of atrial fibrillation (P<0.001) with ivabradine.…”
Section: Adverse Eventsmentioning
confidence: 99%